Morphological and molecular analyses of South American Microliabum (Compositae, Liabeae, Paranepheliinae) and reinstatement of Austroliabum. Issue 6 (17th February 2020) - Gutiérrez, Diego G.; Garcia‐Jacas, Núria; Susanna, Alfonso; Grossi, Mariana A.
Abstract: The small Neotropical tribe Liabeae (Compositae) is currently classified into four subtribes: Liabinae, Munnoziinae, Paranepheliinae, and Sinclairiinae. As currently accepted, Paranepheliinae includes seven genera, Chionoppapus, Erato, Microliabum, Paranephelius, Philoglossa, Pseudonoseris, and Stephanbeckia, distributed especially throughout the Andes from Venezuela and Colombia to Argentina. Our research focuses in the genus Microliabum, which inhabits extra‐Andean enviroments from Bolivia to central Argentina. The broad concept of Microliabum and its phylogenetic position within Paranepheliinae are controversial. Bayesian and maximum parsimony analyses of ribosomal nuclear ITS and plastid trnL ‐ F suggest that both subgenera described within Microliabum are monophyletic. However, Microliabum, without the subgenus Austroliabum, is close to Stephanbeckia . A statistical analysis (PCoA) supports the separation of the subgenera, and morphology mainly based on traits of the involucre and florets permits to establish new taxonomical circumscriptions. Thus, the reinstatement of Austroliabum, the more southern Liabean genus, is here proposed. The genus includes three endemic species from Sub‐Andean and Pampean Hills in central and northwestern Argentina. Austroliabum is characterized by white‐tomentose or woolly pubescence on stems and abaxial leaf surfaces, acrodromous leaf venation, campanulate involucres, coriaceous and adpressed phyllaries in usually five series, outer phyllaries shorter than the inner ones, style branches of disc florets shorter than the pubescent part on the shaft below the bifurcation point, style pubescence on the shaft below the bifurcation point of disc florets at least three times longer than the branches of the style, persistent 2‐seriate pappus with outer series of scales and inner series of barbellate bristles, and achenes pubescent on the ribs. In addition, a revision of Microliabum s.str., with three species, is carried out.